The Survey of the Site and Its Insights - Uziel, Joe (Near Eastern archaeology, 2018)
Since its infancy, archaeological research has used survey as a major tool in both regional studies (see, e.g., Conder and Kitchener 1881) and as a tool for project planning. In the former, survey flourished—despite certain critiques as to the validity of the data collected (e.g., Waelkens and Poblome 2004)—whereas the latter was often used minimally in the interpretation of an individual site's history. In this sense, the survey at Tell eṣ-Ṣâfi/Gath was groundbreaking in its approach— not only as a tool for planning the project, but as the basis for determining aspects of the history of the site (Uziel and Maeir 2005, 2012). The survey was planned by the division of the site into separate fields, based on discrete micro-topographical features. As opposed to an arbitrary grid, the use of the topography of the site considered that these features may have been formed by the changing settlement of the site over time. For example, the eastern slopes (Areas A and E), which have been extensively excavated, each had its own local phasing, which was determined through their separate survey. Had we used a random grid, it is likely the parts of each of these terraced steps would have been lumped together, making the survey a tool for overall evaluation of the site, but not determining differences in the various areas. This proved critical in the planning of the project, which later, through the implementation of the survey results, managed to determine excavation areas according to the research design of the project.